(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To validate a method for the quantification of Meloxicam in film by high performance liquid chromatography in order to contribute to product quality standardization. Subjects and methods: Quantitative Meloxicam by high performance liquid chromatography method with GRACE Apollo C18 (4.6 × 250 mm, 5 µm), flow rate 1.0 ml/min, detector UV at 354 nm, injection volume 10 µl, mobile phase consisting of acetonitril, distilled water and glacial acetic acid (55:40:5). Results: The method ensured suitability, specificity, linearity, repeatability, and precision as specified by ICH. Conclusions: The quantitative method meets the requirements and can be used for the quantification of Meloxicam in film.